2022
DOI: 10.18311/jeoh/2021/28561
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Myofascial Release, Muscle Energy Technique and Stretching of Quadrartus Lumborum Muscle in Patients with Non-Specific Low Back Pain

Abstract: <strong>Background:</strong> Low back pain is attributed to be the most commonly encountered health condition and considered to be one of the leading cause of disability. It is known to occur in all age groups in both developed as well as developing countries. About 80% of the patients have moderate to severe pain affecting their activities of daily living, with females more affected than males. Almost 90% of low back pain is of non-specific type. Quadratus lumborum is one of the deep muscles locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The treatment was given for two weeks. They concluded that MFR stretching and MET when given in combination are effective in the treatment of subjects with NSLBP, As they help treat the tendinitis of the sacroiliac joint stabilizer muscles [32]. Çirak et al researched to check the effect of SNAG on muscles in the lumbar region in terms of stiffness.…”
Section: Author Study Type Studymentioning
confidence: 99%
“…The treatment was given for two weeks. They concluded that MFR stretching and MET when given in combination are effective in the treatment of subjects with NSLBP, As they help treat the tendinitis of the sacroiliac joint stabilizer muscles [32]. Çirak et al researched to check the effect of SNAG on muscles in the lumbar region in terms of stiffness.…”
Section: Author Study Type Studymentioning
confidence: 99%